Social Exclusion and Inclusion in Georgia : A Country Social Analysis - World Bank (World Bank, Washington, DC, 2017)
Georgia has an impressive record of reforms and is on a steady track of poverty reduction, butensuring that of its all citizens can equally benefit from and contribute to its development remains a challenge. This study focuses on one particular aspect of Georgia’s path to inclusive growth: social inclusion. It uses the concepts of social inclusion and exclusion to help understand why some members of society may be consistently left behind from the development process, and to provide insights into policies that can have a transformational impact on the situation of systematically disadvantaged groups and individuals. Social exclusion implies that certain members of society, due to their social or cultural identity, may face complex barriers and, due to them, have persistently lower outcomes— e.g., access to quality education, health, employment, and income—relative to the rest of society, thus not achieving their full potential.